Deep syntactic tree prediction - Výboch, Peter (2019)
In this work, we will be considering one possible implementation of machine learning algorithm for deep syntactic tree prediction. Specifically, we will rely on a tectogrammaticalrepresentation of a dependency relationships of a tectogrammatical tree and test a reasonablycompact solution of said task.In the introduction, we will discuss a historical context of natural language processing andoutline the motivation for this work. In the next chapter tectogrammatical representationand structure of a tectogrammatical tree will be addressed. Further, we will consider sometheoretical preliminaries for the implementation of the neural networks and for a short timeturn to the specifications of a dataset. Then, we will describe the implementation details ofthe data extracting algorithm, as well as the neural network. We will close-off with assessmentof the results, gathered from the tests.